2008
DOI: 10.1146/annurev.publhealth.29.020907.090812
|View full text |Cite
|
Sign up to set email alerts
|

Recent Declines in Chronic Disability in the Elderly U.S. Population: Risk Factors and Future Dynamics

Abstract: As U.S. life expectancy has increased, questions arise as to how the quality of health and functioning in the elderly population has changed. Data from the 1982-2004 National Long-Term Care Survey (NLTCS) suggested that chronic disability prevalence above age 65 declined at an increasing rate with a 2.2% per annum rate of decline from 1999 to 2004 (71). Inflation-adjusted per capita Medicare expenditure rates in nondisabled persons also declined, 0.9% per annum from 1982 to 2004, which suggests that declines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 95 publications
5
103
1
4
Order By: Relevance
“…Currently, there is no conclusive evidence on whether people will age in good or bad health in the future (Bonneux et al, 2012;Lafortune G et al, 2007;Manton 2008). The large baby boom cohorts will push up social services spending, but the extent and amount of such spending growth will depend on whether or not there will be a compression of morbidity and disability in the elderly (Fries et al, 2011;European Commission, 2012;DG ECFIN, 2006;Manton et al, 2007;Spillman, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no conclusive evidence on whether people will age in good or bad health in the future (Bonneux et al, 2012;Lafortune G et al, 2007;Manton 2008). The large baby boom cohorts will push up social services spending, but the extent and amount of such spending growth will depend on whether or not there will be a compression of morbidity and disability in the elderly (Fries et al, 2011;European Commission, 2012;DG ECFIN, 2006;Manton et al, 2007;Spillman, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Although the baseline is very different between countries and the evolution of the health status of their populations is uncertain, the demographic evolution of European countries in the forthcoming decades is expected to pose significant pressure on public budgets regarding pension benefits, health care and LTC costs (DG ECFIN, 2006;Economic Policy Committee, 2009). The evolution of LTC expenditures will be conditioned by several distinct factors: demographics (percentage of the population over 65), institutions (organization of the LTC system, tradeoff between formal and informal care and support for the latter type of care) and health (Spillman, 2004;European Commission, 2007;Lafortune et al, 2007;Manton et al, 2007;Manton, 2008;de Meijer et al, 2011;Jiménez-Martín and Vilaplana-Prieto, 2012). Therefore, ageing of the population will not only challenge the organisation of health care systems but also imply a redefinition of LTC systems in the years to come.…”
Section: Introductionmentioning
confidence: 99%
“…The elderly subjects included in our analysis may however exhibit worse health states than the baby booming cohort will when reaching the same age in the future. Recent supportive evidence of the "Compression of Morbidity" paradigm [25] points to a later onset of many diseases and disability, which has far exceeded the rise in life expectancy during the same period [26-29]. Younger cohorts in developed countries tend to live longer, whereas the time of serious morbidity and especially disability is increasingly getting compressed into the last years of life [30-32].…”
Section: Discussionmentioning
confidence: 99%
“…Increased awareness of healthier lifestyles and medical advancements have created a generation of more active and physiologically fit elderly [3,6,7]. Freedman et al [7] demonstrated in a systematic review that prevalence of disability and functional limitations is declining among the US population, and Manton [14] concluded that chronic disability declined by 2.2% per year from 1999 to 2004. Consequently, an 80-year-old physically active patient may have more physiologic reserve to withstand the stresses of a femoral neck fracture than a deconditioned 80-year-old individual.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty has been associated with short-and long-term all-cause mortality in hospitalized patients older than 64 years [17] and is an accessible tool for estimating individual risks of mortality [16]. In the surgical setting, frailty increases postoperative complications, institutional discharge, inhospital mortality, and length of stay [14,17,23]. The idea of frailty has yet to be applied to mortality after elderly femoral neck fracture.…”
Section: Introductionmentioning
confidence: 99%